Investigation of Biological Activity, Open Porosity and Water Absorption of Ternary Polymeric Blend (Polymethylmethacrylate / Starch) used for Bone Scaffold - Salih, Sihama I.; A. Hashim, Fadhil; J.Eesa, M.; Al-Saedi, Sally A. (The Iraqi Journal of Veterinary Medicine, 2019)
In this study a fabrication of three groups of biological system for bone scaffold, which consist of first group samples (Acrylic bone cement: % X poly methyl meth acrylate ), second group samples (poly methyl meth acrylate: % X Acrylic bone cement), with selected weight percentages of second material are (5, 10,15 and 20 % wt.) and third group, (Acrylic bone cement: 15 % poly methyl meth acrylate : % X starch) with selected weight percentage ratios of starch are (2, 4 and 6 %wt.). In vitro biological activity and water absorption have been studied. The results clarified that the in vitro biological activity test showed that all fabricated samples have no biological influence on the gram positive bacteria Bacillus subtilis and gram negative bacteria Escherichia coli . The results show that the first group of polymer blend have low open porosity and water uptake capacity than a second group. The increasing in starch weight fraction for the third group led to increasing in open porosity and water absorption..